Three lectures - Mathew, K. K. (Lucknow, 1983)
This book contains the Cochin University Public Law Lectures, 1979 delivered by the author at the Uni versity Department of Law. The first lecture is a probe into the juristic technique of reconciling the tradi tional judicial function with modern trends of judicial activitism. In the second lecture the author examines how natural law is useful in evaluating positive law. In the third lecture he delves into controversial areas like the right to rebellion and the limits of obedience to superior orders.
Keywords: Law